Prevalence and survival of Salmonella spp. in raw chicken: risks in online delivery and storage systems - Alia Syafieqah Zulkifli; Sahilah Abd Mutalib; Muhamad Firdaus Syahmi Sam-On; Nurul Aqilah Mohd Zaini (Penerbit Universiti Kebangsaan Malaysia, 2025)
Nontyphoidal Salmonella is one of the most significant foodborne pathogens found mainly in poultry, with Salmonella enterica subp. enterica serovar Typhimurium is the most common cause of poultry-related outbreaks. This study aimed to determine the prevalence of Salmonella spp. and S. Typhimurium in raw chicken purchased from online stores and to evaluate the shelf-life of raw chicken stored in frozen (-18 °C) and chilled (4 °C) conditions. A total of twenty-seven (n=27) samples were purchased in three consecutive months. Detection of Salmonella spp. and S. Typhimurium were determined using standard ISO 6579-1:2017 and molecular methods. Results show that all brands purchased online were contaminated with Salmonella spp. and S. Typhimurium, with Brand B exhibiting the highest prevalence of Salmonella spp. (100%) and Brand A, showing the highest prevalence of S. Typhimurium (66.7%). Chicken wings showed significantly higher contamination (p < 0.05) compared to breast and thigh parts. Shelf-life analysis combined with predictive modelling showed that freezing is effective in preserving raw chicken, with a daily inactivation rate of Total Viable Count (TVC) (0.23%) and Salmonella spp. (0.45%), which is also predicted to be safely stored up to 9 months in a freezer. Under chilled storage, the raw chicken acceptance limit was 0.38 days (≤ log 5 cfu/g), while the spoilage threshold was 4.2 days (≥ log 7 cfu/g). The results of this study suggest that raw chicken purchased from online stores is potentially contaminated with Salmonella spp. thus, safe handling and delivery need to be practised to reduce the risk.